Impact of Artifacts Caused by Intraoral Dental Materials in Magnetic Resonance Imaging - Divya Josephraj; Ravindranath Vineetha; Priya Pattath Sankaran; Prakashini Koteshwara; Mathangi Kumar; Kalyana Chakravarthy Pentapati (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the characteristics of artifacts produced by various intraoral dental materials in magnetic resonance imaging sequences and assess their impact on the diagnostic quality of the resultant images. Material and Methods: A clinical examination was conducted on forty-six patients who underwent magnetic resonance imaging for various brain pathologies. Parameters were recorded, including the location, span, and type of intraoral dental material. The impact of these artifacts on the diagnostic quality of the resultant image sequences was assessed. The reliability of the intra- and interobserver was calculated, and Fischer's exact test was applied. P-value <0.05 was considered statistically significant. Results: The most common signal intensity artifact observed was hypointense with hyperintense rim artifacts in FLAIR (95.5%). The most common shape of the artifacts observed was circular/void shape (84.4%). There was a statistically significant difference between the various classes of intraoral dental materials and diagnostic acceptability (p=0.017). In the present study, 28% of the study population images were graded diagnostically unacceptable in the sequences evaluated (FLAIR 37.8%, T2 3.3%, SWI 24.4%, DWI 25%). Conclusion: Dental material artifacts interfered with the interpretation of magnetic resonance imaging at varying levels of diagnostic acceptability depending on the indication for which the imaging was performed.